Individualized Exercise Training at Maximal Fat Oxidation Combined with Fruit and Vegetable-Rich Diet in Overweight or Obese Women: The LIPOXmax-Réunion Randomized Controlled Trial. - Florent Besnier; Victorine Lenclume; Patrick Gérardin; Adrian Fianu; Jérémy Martinez; Nadège Naty; Sylvaine Porcherat; Karim Boussaid; Stéphane Schneebeli; Eric Jarlet; Sarah Hatia; Georges Dalleau; et al. (PLoS ONE, 2015)
Lifestyle combined interventions are a key strategy for preventing type-2 diabetes (T2DM) in overweight or obese subjects. In this framework, LIPOXmax individualized training, based on maximal fat oxidation [MFO], may be a promising intervention to promote fat mass (FM) reduction and prevent T2DM. Our primary objective was to compare three training programs of physical activity combined with a fruit- and vegetable-rich diet in reducing FM in overweight or obese women.A five months non-blinded randomized controlled trial (RCT) with three parallel groups in La Réunion Island, a region where metabolic diseases are highly prevalent.One hundred and thirty-six non-diabetic obese (body mass index [BMI]: 27-40 kg/m2) young women (aged 20-40) were randomized (G1: MFO intensity; G2: 60% of VO2-peak intensity; G3: free moderate-intensity at-home exercise following good physical practices).Anthropometry (BMI, bodyweight, FM, fat-free mass), glucose (fasting plasma glucose, insulin, HOMA-IR) and lipid (cholesterol and triglycerides) profiles, and MFO values were measured at month-0, month-3 and month-5.At month-5, among 109 women assessed on body composition, the three groups exhibited a significant FM reduction over time (G1: -4.1±0.54 kg; G2: -4.7±0.53 kg; G3: -3.5±0.78 kg, p<0.001, respectively) without inter-group differences (p = 0.135). All groups exhibited significant reductions in insulin levels or HOMA-IR index, and higher MFO values over time (p<0.001, respectively) but glucose control improvement was higher in G1 than in G3 while MFO values were higher in G1 than in G2 and G3. Changes in other outcome measures and inter-group differences were not significant.In our RCT the LIPOXmax intervention did not show a superiority in reducing FM in overweight or obese women but is associated with higher MFO and better glucose control improvements. Other studies are required before proposing LIPOXmax training for the prevention of T2DM in overweight or obese women.ClincialTrials.gov NCT01464073.